Enzymatic esterification of kojic acid and palmitic acid by immobilized lipase for synthesis of kojic acid palmitate - Ishak, Nurazwa (2015)
Kojic acid (5-hydroxy-2-hydroxymethyl-4-pyrone) is an organic acid produced from various carbon sources in an aerobic fermentation by many species of Aspergillus, Penicillium and Acetobacter. The importance of kojic acid (KA) is recently focused on its role as whitening agent in cosmetic formulation. Kojic acid is water soluble and has low stability towards light exposure. KA has also been criticized for weak depigmenting effect and unstable for long storage. The hydrophilic property of KA has restricted its application in cosmetic, oily food and pharmaceutical products. In order to improve the chemical and biological activities of KA, its derivatives with new and improved chemical properties and biological activities needs to be developed. Various KA derivatives such as KA esters have been synthesized at industrial scale. KA esters are normally produced via chemical process where strong acid or alkali is used. This chemical process is not environmentally friendly and also produces complex mixtures that make the product purification difficult and high cost. The possibility of using lipase, lipozyme RMIM, in the esterification of KA with palmitic acid (PA) in acetone to synthesize KA palmitate (KAP) was investigated in this study. Preliminary, the effects of organic solvent, substrate ratio, enzyme loading, temperature and reaction time on the yield of KAP were evaluated. The appropriate ranges for each variable were subsequently used for optimization using response surface methodology (RSM). The optimal reaction condition for ester production was then applied in 500 mL stirred tank reactor (STR) using two types of impeller [Rushton turbine (RT) and Pitch blade disc turbine (PBDT)] to investigate the effect of agitation speed on the esterification performance. Among the organic solvent tested for esterification to synthesize KAP, acetone was the preferred solvent. Optimal conditions for esterification as suggested by RSM were as follows: PA to KA ratio, 6.74; enzyme loading, 0.59 g; reaction temperature, 45.9°C and reaction time, 20 h, which gave the percentage of esterification of 64.47%. For the esterification in STR, the percentage yield of KAP was significantly higher for RT than PBDT at all agitation speeds tested (150 to 450 rpm). The highest yield of KAP (82.14%) was obtained in STR with RT agitated at 250 rpm. Results from this study have demonstrated that substantially high yield of KA esters could be produced by enzymatic esterification using lipase. This alternative method has potential to be used industrially. Since the use of hazardous chemical can be minimized, enzymatic synthesis of KA esters is more natural and appears to be more appealing to the customers than the chemical process.